Overuse of organ biopsies in immunoglobulin light chain amyloidosis (AL): the consequence of failure of early recognition. (3rd October 2017) - Muchtar, Eli; Dispenzieri, Angela; Lacy, Martha Q.; Buadi, Francis K.; Kapoor, Prashant; Hayman, Suzanne R.; Gonsalves, Wilson; Warsame, Rahma; Kourelis, Taxiarchis V.; Chakraborty, Rajshekhar; Russell, Stephen; Lust, John A.; et al.
Abstract: Introduction: The diagnosis of amyloidosis requires histological confirmation of Congo-red (CR) deposits. The tissue source is preferably fat aspiration and/or bone marrow (BM) biopsy, but at times organ biopsy is required. Methods: We studied 612 patients with systemic immunoglobulin light chain amyloidosis to characterise the tissues used to establish the diagnosis. Results: The median number of tissue samples was 3. About 95% of BM biopsies were stained for CR, while 79% of patients had fat aspiration CR-stained. CR stain sensitivity was 69% in BM, 75% in fat aspiration and 89% for both sources combined. In comparison, CR sensitivity was 97–100% for heart, renal and liver biopsies. About 42% of patients with renal involvement, 21% of patients with liver involvement and 13% of patients with heart involvement underwent organ biopsy, when a less invasive biopsy would have established the diagnosis. Predictors for the requirement for organ biopsy were male sex, limited organ involvement and lack of fat aspiration. Discussion: Fat aspiration is underutilised for histologic confirmation of amyloidosis. A high rate of organ biopsies represents a failure to recognise the disease. Early awareness of amyloidosis in patients with organ dysfunction may lead to more judicious use of organ biopsies in this disease. Key messages: Fat pad aspiration is underutilised to establish the diagnosis of amyloidosis. Bone marrow and fat pad aspiration obviates the need for invasive biopsies. The excessive use of organ biopsy in AL amyloidosis reflects failure to recognise the disease early in its course.